2018
DOI: 10.1007/s10898-018-0634-1
|View full text |Cite
|
Sign up to set email alerts
|

A sampling-based exact algorithm for the solution of the minimax diameter clustering problem

Abstract: We consider the problem of clustering a set of points so as to minimize the maximum intra-cluster dissimilarity, which is strongly NP-hard. Exact algorithms for this problem can handle datasets containing up to a few thousand observations, largely insufficient for the nowadays needs. The most popular heuristic for this problem, the complete-linkage hierarchical algorithm, provides feasible solutions that are usually far from optimal. We introduce a sampling-based exact algorithm aimed at solving large-sized da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…We have observed that, in a large number of iterations, the optimal value of problem pDP(D, p) does not decrease from one iteration to the next. This type of dual degeneracy is often observed in decremental relaxation schemes (Aloise andContardo 2018, Contardo et al 2019). Therefore, before resorting to executing the exact solver described in the previous section, our heuristic scheme checks if it is possible to select p points out of the p + 1 points identified from the previous iteration-which includes p − 1 optimal clusters that remain untouched plus the one that has been split into two-as described in Section 3.4.…”
Section: Procedures Solvepdp(d # P)mentioning
confidence: 81%
See 2 more Smart Citations
“…We have observed that, in a large number of iterations, the optimal value of problem pDP(D, p) does not decrease from one iteration to the next. This type of dual degeneracy is often observed in decremental relaxation schemes (Aloise andContardo 2018, Contardo et al 2019). Therefore, before resorting to executing the exact solver described in the previous section, our heuristic scheme checks if it is possible to select p points out of the p + 1 points identified from the previous iteration-which includes p − 1 optimal clusters that remain untouched plus the one that has been split into two-as described in Section 3.4.…”
Section: Procedures Solvepdp(d # P)mentioning
confidence: 81%
“…2, pp. 134-144, © 2020 observed and reported for other relaxation-based methods for minimax and maximin combinatorial optimization problems (Aloise andContardo 2018, Contardo et al 2019); it seems to be related to the dual degeneracy occurring when a larger number of clusters can be rearranged from one iteration to the next to find solutions of the same cost. This type of degeneracy occurs at a much smaller scale when the target number of points p is small.…”
Section: Computational Experiencementioning
confidence: 85%
See 1 more Smart Citation
“…-The subject of the paper [4] by Sonia Cafieri and Claudia D'Ambrosio consists of using feasibility pump heuristics for the problem of aircraft conflict avoidance arising in air traffic management; -M. Fernanda P. Costa, Ana Maria A.C. Rocha and Edite M.G.P. Fernandes investigate in [5] the use of a filter methodology in the DIRECT method to assure convergence in nonconvex constrained global optimization problems; -The paper [6] by Angelo Lucia, Peter A. DiMaggio and Diego Alonso-Martinez considers a new approach to metabolic network analysis using a Nash Equilibrium formulation; -Immanuel M. Bomze, Vaithilingam Jeyakumar and Guoyin Li in their paper [7] guarantee exact copositive and Lagrangian relaxations to extended trust region problems with one or two balls; -The paper [8] by Jan Kronqvist, Andreas Lundel and Tapio Westerlund discusses reformulations for utilizing separability when solving convex mixed-integer nonlinear programming problems; -Two feasibility heuristics based on the integrality gap minimization for binary mixedinteger nonlinear programming are discussed in the paper [9] by Wendel Melo, Marcia Fampa and Fernanda Raupp; -A sampling-based exact algorithm for the solution of the minimax diameter clustering problem is proposed in the paper [10] by Daniel Aloise and Claudio Contardo; -J. J. Moreno, Gloria Ortega, Ernestas Filatovas, J. A. Martínez and E. M. Garzón in their paper [11] discuss the improvement of the performance and energy of non-dominated sorting for evolutionary multiobjective optimization on GPU/CPU platforms.…”
mentioning
confidence: 99%
“…Uma estratégia amplamente utilizada para melhorar a eficiência dos algoritmos de agrupamento é a redução do número de elementos submetidos a esses algoritmos. Essa redução é obtida por meio de técnicas, tal como, amostragem (ALOISE; CONTARDO, 2018). Esse tipo de técnica mostrou-se útil para os métodos que realizam várias iterações considerando diferentes inicializações, como o algoritmo PAM.…”
Section: Estratégias De Otimizaçãounclassified